Argumentation methods in educational contexts: Introduction to the special issue. (2016) - Rapanta, Chrysi; Macagno, Fabrizio
Highlights: Provide an explanation for the need of a more thorough discussion between the fields of argumentation theory and educational practice. Present an overview of the research areas in which such intersection is necessary. Describe the rationale of the articles included in the special issue. Abstract: The relation between argumentation and education is currently attracting researchers' attention from both argumentation theory and educational practice fields. Although much work has been done in the intersection between methods of analyzing and assessing arguments and their emergence in educational contexts, there is still a lack of clarity regarding how the philosophical and logical tradition can feed educational practice and vice versa. This introduction of the special issue on " Argumentation methods in educational contexts " is aimed at explaining the need for more systematic discussions between the two sub-fields. The paper concludes with an overview of the five articles that form part of this special issue, which separately represent directions for future research in the field of argument in education.